UJI KETAHANAN LUNTUR WARNA PADA KAIN DENGAN PEWARNA DARI EKSTRAK UBI UNGU - Ery Fatarina Purwaningtyas; Ahmad Shobib; Noormi Handayani (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
One of the cheap and widely available sources of anthocyanins in Indonesia is purple sweet potatoes because purple sweet potatoes contain anthocyanins that are greater than sweet potatoes with other varieties. This research conducted anthocyanin extract from purple sweet potato using technical extract tables using solvent methanol. The coloring process is carried out from pre-mordant without mordant. The compound used is alum. In the process of dyeing the cloth in the anthocyanin extract, the soaking time was varied, namely 12, 18, 24 and 30 hours. Furthermore, it was tested for color fastness against washing, staining, wet rubbing and dry rubbing.From the results of the study, the average anthocyanin content of purple sweet potato was 174.085 mg/100 g of dry matter.The results of the application of dye from sweet potato extract showed thatthe immersion time, pre-mordanting treatment and without mordant had no effect on the results of the color fastness test against washing, staining and dry rubbing. The results of the color fastness test to washing at 40°C gave a value of 1-2 or